Control of high voltage direct current (HVDC) systems - Muhammad Rashid Mohamed Fadiah. (2010)
The project progress, research, and data of a High Voltage Direct Current (HVDC) system is summarized in this report, with main focuses on the converters and the control system, process and development of the software components that is used to control the output electrical power supply. A detailed close loop control technique to provide good voltage and frequency control has been worked out. The major components involved in the control technique has been configured and tested. Such as the Kp, Ki and KD which are the values for the Proportional controller, Integral controller and the derivative controller. The aim of this entire project is to develop a control strategy that is able to generate a stable output of electrical power to the grid system at the output.